Pengaruh Penggunaan Media Sosial, Entrepreneurial Literacy dan Digital Literacy Terhadap Minat Berwirausaha Mahasiswa Universitas Dharma Andalas - Fajrian Afda; Lasti Yossi Hastini (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research is a survey study of students at Dharma Andalas University. This research is titled "The Influence of Social Media Use, Entrepreneurial Literacy, and Digital Literacy on the Entrepreneurial Interest of Students at Dharma Andalas University." The purpose of this research is to determine the influence of social media use, entrepreneurial literacy, and digital literacy on the entrepreneurial interest of students at Dharma Andalas University. The type of this research is quantitative research, and the data collection method uses a questionnaire. The population in this study consists of 2,147 students from Dharma Andalas University. The number of samples taken in this study is 131 respondents. The sampling technique used is Non-Probability Sampling with the Snowball Sampling method. Based on the research results and data analysis using SPSS version 25, it shows that: (1) The use of social media has a positive and significant effect on the entrepreneurial interest of students at Dharma Andalas University, (2) Entrepreneurial literacy has a positive and significant effect on the entrepreneurial interest of students at Dharma Andalas University, (3) Digital literacy has a positive and significant effect on the entrepreneurial interest of students at Dharma Andalas University, (4) The use of social media, entrepreneurial literacy, and digital literacy has a positive and significant effect on the entrepreneurial interest of students at Dharma Andalas University.